Effect of glass fibers on mechanical properties of structural lightweight foamed concrete(SLFC) (University of Thi-Qar Journal for Engineering Sciences, 2013)
Lightweight foamed concrete exhibits many advantages and excellent features comprising more efficient strength-to-weight ratio in structural elements, high strength, reduced dead load, decrease foundation loads, energy saving, waste consuming, temperature conservation, and noise insulation. This work was prepared to investigate the effect of glass fibers on mechanical properties of structural lightweight foamed concrete (SLFC), Foam agent (organic material) was used to produce SLFC using different mix proportions to obtain structural compressive strength and high workability with slightest fresh density. Five mixes of SLFC with Superplasticizer is experimentally studied, also five mixes without Superplasticizer were tested. The compressive strength, flexural strength, ultrasonic pulse velocity (UPV), workability (flowability) and density were measured. Superplasticizer used in some mixes was 1% by weight of cement. Glass fibers were added in different volume fraction for SLFC and SLFC with superplasticizer. The volume fractions of the glass fibers used are: 0.06, 0.2, 0.4, and 0.6 % total volume. The results of SLFC mixes showed that the increase of glass fibers content can produce foam concrete with enhanced mechanical properties. For all percentages of glass fibers in the mixes it increases in compressive strength and flexural strength. But the increase in compressive strength was 51% for 0.6% glass fibers. Also the flexural strength increased 19.2% for 0.6% glass fibers. The compressive and flexural strength increased with the increase of glass fibers with acceptable range of workability.